Foreign Policy Thought as System and Process: I.G. Tyulin on the Mechanisms Shaping the Ideological Foundations of French Foreign Policy - P. A. Tsygankov (Vestnik MGIMO-Universiteta, 2025)
This article provides a detailed analytical commentary on the key concepts, ideas, and theoretical constructs developed by I.G. Tyulin in his doctoral dissertation, which examined the formation and evolution of French theories of international relations and foreign policy thought as of the late 1980s. The central research question is whether the issues and arguments presented in his work regarding the evolution of French foreign policy thought remain relevant in the fundamentally transformed conditions of the present day. To address this question, the study employs textual and comparative historical methods.The first section, dedicated to methodology, focuses on Tyulin’s demonstration of the extent to which French foreign policy thought is shaped by national cultural traditions and its analysis as an integrated ideological and theoretical system. The second section explores the role of theories and concepts within the structure of French foreign policy thought and the institutional mechanisms that shaped its formation and evolution as of the late 1980s. The third section offers a concise overview of subsequent developments in the institutional and theoretical-conceptual landscape of contemporary French foreign policy thought.An analysis of these transformations, viewed through the lens of Tyulin’s work, reveals that the ideological and theoretical production processes he identified continue to manifest in modern France. Core characteristics—such as sociologism, a strong emphasis on identity positioning, statism, internal contradictions, and the predominance of political realism—persist, albeit within a new, ultra-liberal context. This shift influences the content of theories, conceptual frameworks, socio-political debates, and the ways in which participants articulate their perspectives.The study ultimately concludes that Tyulin’s dissertation presents a nuanced yet coherent portrait of French foreign policy thought. His analysis provides essential insights into the formation and evolution of this intellectual tradition, without which it is difficult to fully grasp the contemporary dynamics of France’s foreign policy trajectory.